Association between parenting styles and adolescents’ mental disorders: findings among pre-university students - Mohd Arifin, Siti Roshaidai; Syaziman, Nur Syila Syahida; Abang Abdullah, Khadijah Hasanah; Abd Aziz, Karimah Hanim; Che Mat, Khairi; Muhammad, Noor Azimah; Wardaningsih, Shanti (Penerbit Universiti Sains Malaysia, 2024)
Background: Existing research indicated a high prevalence of mental health issues among adolescents. Gender and parenting styles are two factors that may influence adolescents’ mental health. Nonetheless, most published studies focused on either secondary school or university students. In contrast, there is a dearth of similar research involving pre-university students. This study aimed to determine the prevalence of mental disorders among pre-university students and their association with parenting styles. Methods: A cross-sectional study via online questionnaire survey was conducted among students from a pre-university college on the East Coast of Malaysia. Convenience sampling was used to recruit the participants. The questionnaire consisted of three parts: i) sociodemographic data, ii) the Parental Authority Questionnaire and Depression, and iii) the Anxiety and Stress Scale (DASS-21). An online invitation to answer the questionnaire was done via the Student Representative Council (SRC). Data were analysed using descriptive statistics and Pearson’s chi square test. Results: A total of 431 participants responded to the online survey. The prevalence of depression, anxiety and stress was 49.0% (n = 210), 68.0% (n = 293) and 37.6% (n = 162), respectively. In addition, father’s educational level (² = 10.332, P = 0.001) and the authoritarian parenting style (² = 10.099, P = 0.006) were significantly associated with mental health disorders among adolescents. Conclusion: The prevalence of mental disorders among pre-university students is relatively high. Pre-university admission mental health screening is vital for early detection and intervention of mental disorders among this vulnerable group. Further research is imperative to establish a comprehensive plan of action that targets parental involvement in managing adolescent mental health disorders.